Historia Política - Todd, Roberto H. (My University, 1923)
Artículo sobre "renuncia" del Gabinete Autonómico en 1899.
Keywords: Political parties--Puerto Rico.; Partido Liberal Puertorriqueño; Partido Republicano (Puerto Rico); Partido Unión de Puerto Rico; Partido Socialista Puertorriqueño.; Brooke, John R.; McIntyre, Frank; Muñoz Rivera, Luis, 1859-1916; Coll y Toste, Cayetano, 1850-1930; Hernández López, Juan